Bird Flu and Bangladesh: Review and Update - Ahmed, ASM Nawshad Uddin (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Bird flu is an infectious disease of birds caused by Influenza A (H5N1) virus. Although the virus usually do not infect humans, more than 200 confirmed human cases of Avian Influenza A have been reported worldwide. Almost all of them had caught it from birds. While H5N1 undergoes specific mutations and reassorting creating variations which can infect species not previously known to carry the virus, health experts fear the virus could trigger a pandemic if it mutates to form a strain that can transmit between humans. As bird flu confirmed in about 59 countries, it is extremely pathogenic, humans do not possess any immunity to it, currently no vaccine is available and sometimes H5N1 can become resistant to the antivirals, a global pandemic would kill millions of people. A human pandemic would be particularly catastrophic in developing countries where living conditions and malnutrition are likely to make people more vulnerable, health services are weak and vaccines and antivirals would be beyond reach. Recently bird flu has been detected in Bangladesh, which may lead to devastating consequences on the health of the people and economy of the country. So every effort should be taken to prevent its further spread, make people aware of the disease, training health personnel and stockpiling antivirals to face any human epidemic. DOI: 10.3329/jbcps.v26i1.4231 J Bangladesh Coll Phys Surg 2008; 26: 32-38